Medical Management of Blockchain, Patients, and Clinical Studies - Wang, Shih-Shuan; Dinu, Alexandru; Toth, Zsolt; Boscoianu, Mircea (Journal RECENT, 2023)
There are procedures and rules that must be followed throughout clinical examinations and investigation, which is a lengthy, intricate procedure. From the early registration processes, informed consent, clinical data, and the moment at which post-marketing authorisation is granted, and publishing, there are concerns regarding the openness of clinical research data. As a result, persons using authorized medications have had various effects, some of which have been deadly. These impacts are said to appear as fraud, bad conduct, selective reporting, bias, and other things. It has also been challenging to get access to research data from people participating within clinical studies include patients and even academics who could be intrigued by the post-marketing period and pharmacological analyses. Data gathered from reliable sources that highlight the registration-related risks are offered as evidence. A current illustration of how lack of openness has led to a severe problem with opioid usage is a conscious decision and the manner in which clinical study results are publicized considering the usage of blockchain is being considered as a mechanism or framework for clinical research institutions, regulatory and nonregulatory bodies, pharmaceutical associations, medication manufacturers/suppliers, and patients. In order to address the difficulties raised, this article introduces a theoretical model that proposes how blockchain might give a more open and secure solution.
Keywords: clinical trials; fraud and misconduct; blockchain; integrity of data; wearables with traceability